A Look at How Climate Bonds Can Help Emerging Markets Grow Their Economy- An Analysis Based on Newly Industrialised Countries (NICs) - S, Nithin.; Shrishti, Kumari; Roy Chowdhury, Piyali (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This current study investigates the key causes that have been driving the green bond market over the past several years, as well as the constraints that prohibit emerging nations from accessing this market. A greater awareness of climate change among investors appears to be supporting the development of green bonds, which appear to be a reality in both developed and developing nations. It also indicates that climate bonds are becoming more prevalent in the financial market. On the other hand, the market in developing countries is still in its early phases, and it appears that its full potential is not being fully appreciated. The key difficulties inhibiting the growth of green bonds in developing nations include the lack of appropriate institutional structures for managing climate bonds, the issue of minimum size requirements, and the high transaction costs associated with issuing these bonds. These difficulties are preventing the growth of climate bonds in developing countries. Overall, the current study focuses on specifying investment strategies for climate bonds that are essential for NICs. The study focusses on establishing a relationship among climate bonds and the economic growth of NICs, using data from 2014 to 2023, with respect to the Great British Pound (GBP), Euro (EUR), Chinese Yuan (CNY), and Japanese Yen (JPY). The integration of the data resulted in a model analysis using the Panel Auto Regressive Distributed Lag (PARDL), which ultimately demonstrates that EUR- and CNY-issued climate bonds have the most significant impact on developing economies. This will ultimately help a country to concentrate on sustainable economic development built on the climate finance bonds, giving priority in these two currencies. Furthermore, it will ultimately reduce the need for unnecessary foreign aid – an external burden for growing economies.